1996
DOI: 10.1016/0014-5793(96)00846-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential translocation of protein kinase C isozymes in rats characterized by a chronic lack of LTP induction and cognitive impairment

Abstract: The translocation of protein kinase C isozymes was investigated in an animal model of cognitive deficit and lack of induction of long-term potentiation (LTP). In MAM rats, presynaptic o, 6, E PKC showed enhanced translocation, while postsynaptic ~ PKC displayed decreased translocation when compared to control levels. This imbalance of PKC isozyme translocation between the pre-and post-synaptic compartment might therefore represent a possible molecular cause for the lack of synaptic plasticity observed in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…This modified translocation is common to all PKC isoforms measured in synaptosomes, i.e. a and p (Ca2+-dependent) and E (Ca2+-independent) isoenzymes (Caputi et al, 1996). In addition, PKC substrates specifically localized at the presynaptic level, such as B-50/GAP-43, show a higher degree of phosphorylation in basal conditions .…”
mentioning
confidence: 98%
“…This modified translocation is common to all PKC isoforms measured in synaptosomes, i.e. a and p (Ca2+-dependent) and E (Ca2+-independent) isoenzymes (Caputi et al, 1996). In addition, PKC substrates specifically localized at the presynaptic level, such as B-50/GAP-43, show a higher degree of phosphorylation in basal conditions .…”
mentioning
confidence: 98%
“…More relevant in this respect are the data on the activity of PKC in the postsynaptic compartment. We have shown that the amount of membrane-bound yisoform of PKC is significantly lower in MAM-treated rats than in controls [38], As mentioned previously, the yisoform of PKC seems to play an important role in LTP [26], and its decrease in MAM-treated rats may therefore account for the lack of activity-dependent synaptic plas ticity. Whether this decrease results in a concomitant decrease in the phosphorylation state of PKC substrates, such as neurogranin and/or glutamate receptors, is cur rently under investigation in our laboratory.…”
Section: Investigation Of the Role Of P K C And Other Kinases In Synamentioning
confidence: 72%
“…Indeed, the amount of PKC localized in the membrane compartment of synaptosomes is signifi cantly increased, and this enhancement is paralleled by an equivalent decrease in levels of PKC in the cytosolic com partment. Moreover, all of the isoforms present in the nerve terminals (a, (3 and e) seem to be equally affected [38]. In addition, PKC substrates that are specifically localized at a presynaptic level, such as B-50, show a high er degree of phosphorylation in basal conditions [39].…”
Section: Investigation Of the Role Of P K C And Other Kinases In Synamentioning
confidence: 99%
“…Additionally, the brains of MAM-treated rats are characterized by a variety of electrophysiological and biochemical abnormalities. A series of elegant studies demonstrated that protein kinase C (PKC)-activity is increased (Cattabeni et al, 1994;Di Luca et al, 1995, 1997 and that PKC-isoforms are differentially translocated in the hypoplastic neocortex of MAM-treated rats (Caputi et al, 1996). This allowed to test the hypothesis that also under in vivo conditions PKC affects the proteolytic processing of the amyloid precursor protein (APP) , which has been implicated in the pathogenesis of Alzheimer's disease (for review see De Strooper et al, 1995;Fowler, 1997;Coughlan and Breen, 2000;Jolly-Tornetta and Wolf, 2000).…”
Section: Introductionmentioning
confidence: 99%